Restless Legs Syndrome and Periodic Limb Movements of Sleep: From Neurophysiology to Clinical Practice. Issue 3 (15th March 2023) - Kouri, Ioanna; Junna, Mithri R.; Lipford, Melissa C.
Summary: This article summarizes restless legs syndrome (RLS), periodic limb movements of sleep, and periodic limb movement disorder. RLS is a common sleep disorder with a prevalence of 5% to 15% in the general population. RLS can present in childhood, and incidence increases with age. RLS can be idiopathic or secondary to iron deficiency, chronic renal failure, peripheral neuropathy, and medications such as antidepressants (with higher rates for mirtazapine and venlafaxine, while bupropion may reduce symptoms at least in the short term), dopamine antagonists (neuroleptic antipsychotic agents and antinausea medications), and possibly antihistamines. Management includes pharmacologic agents (dopaminergic agents, alpha-2 delta calcium channel ligands, opioids, benzodiazepines) and nonpharmacologic therapies (iron supplementation, behavioral management). Periodic limb movements of sleep are an electrophysiologic finding commonly accompanying RLS. On the other hand, most individuals with periodic limb movements of sleep do not have RLS. The clinical significance of the movements has been argued. Periodic limb movement disorder is a distinct sleep disorder that arises in individuals without RLS and is a diagnosis of exclusion.